Acquired Factor V Inhibitor Complicated with Immune Thrombocytopenia - Mima, Fuka; Minami, Ryota; Asako, Mizuki; Matsunaga, Hitomi; Fujita, Yuri; Takimoto, Yoshimi; Senda, Sonoko; Nakahara, Wataru; Ikeda, Mako; Ueda, Shuji (Internal Medicine, 2022)
We herein report a patient with a high bleeding tendency as a result of acquired factor V inhibitor and immune thrombocytopenia (ITP). The administration of prednisolone increased the platelet count, but a fatal bleeding event occurred before platelet levels had sufficiently increased. Factor V is stored in not only plasma but also platelets, and platelet-derived factor V might play a local hemostatic role. Bleeding tendency may be high in rare cases where factor V inhibitor is complicated with severe thrombocytopenia. In such patients, physicians should consider aggressive hemostatic therapy, including plasma exchange, in addition to immunosuppressive therapy.